2012
DOI: 10.1002/jcb.23459
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of titin protein isoform and alternative splicing in normal and mutant rats

Abstract: Titin is a giant protein with multiple functions in cardiac and skeletal muscles. Rat cardiac titin undergoes developmental isoform transition from the neonatal 3.7 MDa N2BA isoform to primarily the adult 2.97 MDa N2B isoform. An autosomal dominant mutation dramatically altered this transformation. Titins from eight skeletal muscles: Tibialis Anterior (TA), Longissimus Dorsi (LD) and Gastrocnemius (GA), Extensor Digitorum Longus (ED), Soleus (SO), Psoas (PS), Extensor Oblique (EO), and Diaphram (DI) were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…As has been reported previously, wild-type (WT) TA expresses two titin isoforms at ~3.44 MDa and ~3.30 MDa, while homozygous (HM) muscles express the much larger titin isoform at ~3.75 MDa[14]. As is illustrated by the SDS-PAGE analysis of a TA muscle in Figure 1B, overall myofilament protein isoform expression was comparable between Wt and HM TA muscles.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…As has been reported previously, wild-type (WT) TA expresses two titin isoforms at ~3.44 MDa and ~3.30 MDa, while homozygous (HM) muscles express the much larger titin isoform at ~3.75 MDa[14]. As is illustrated by the SDS-PAGE analysis of a TA muscle in Figure 1B, overall myofilament protein isoform expression was comparable between Wt and HM TA muscles.…”
Section: Resultssupporting
confidence: 79%
“…In the rat, titin undergoes developmental isoform changes; the longest isoforms are expressed during the embryonic stages and progressively get replaced by shorter isoforms[12, 13]. A recent investigation on the length of the titin isoforms in various muscles during development in both wild-type (WT) and HM rats showed that among all of the skeletal muscle examined in WT rats, the tibialis anterior (TA) undergoes the greatest extent of developmental shortening[14]. The TA titin isoform starts out at 3.7 MDa after birth, and by 180 days there are two shorter isoforms present, a 3.42 MDa isoform and a more abundant 3.29 MDa isoform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using human and animal skeletal muscle myosin heavy chain (205 kDa) and, nebulin (770-890 kDa), as well as the N2A titin isoform (∼3600 kDa and 3700 kDa) of rabbit and human soleus as standards Krüger et al 1991;Granzier and Wang 1993;Prado et al 2005), we estimated that the NT have a Mr of ∼3.8-3.9 × 10 6 (Vikhlyantsev and Podlubnaya 2006). Expression of titin isoforms with these molecular weights is not excluded (Bang et al 2001;Guo et al 2010Guo et al , 2012Li et al 2012), but titin aggregates in gels could not be excluded either (Granzier and Wang 1993;Cazorla et al 2000;Warren et al 2003a). Assuming that molecular masses of titin aggregates should considerably exceed 3800-3900 kDa, we decided to find out more about the differences in electrophoretic mobility of the observed bands.…”
Section: Electrophoretic Detection Of Titin Isoformsmentioning
confidence: 97%
“…Giant titin isoforms expressed in rat striated muscles with an RBM20 autosomal dominant mutation were recently reported (Greaser et al 2008;Li et al 2012;Guo et al 2012). The molecular masses of these isoforms were estimated from their electrophoretic mobility in 1% vertical agarose gel to be 3750 kDa and 3830 kDa ).…”
Section: Electrophoretic Detection Of Titin Isoformsmentioning
confidence: 99%